Complexity Economics as Heterodoxy: Theory and Policy. Issue 4 (2nd October 2017) - Elsner, Wolfram
Abstract: Complexity economics has quickly become a powerful research program for real-world economics in recent years. This article provides an overview of complexity economics, and argues that it is incompatible with the "equilibrium" and "optimality" conceptions of the mainstream and its "market economy." Instead, it develops older heterodox — including evolutionary-institutional — issues like self-organization, emergence, path‑dependence, idiosyncrasies, lock-ins, or skewed power distributions. Also, the space for emergent institutions through the "intentionality" of agents, including their improving collective performance, reducing complexity, and others, is investigated. This article considers complex adaptive systems through "games on networks" in an "evolution-of-cooperation" perspective. Moreover, a surge in policy implications of economic complexity has emerged, even if still rather general. With some more specific implications derived, the article again reveals the close similarities with long-standing heterodoxies: namely, pragmatist policy conceptions in this respect.